Adoption of Design for Environment Practices in the Electronics Industry: A Case Study - Jr, M.J. Alves-Pinto; Mendes, J.V. (Journal of Environmental Accounting and Management, 2026)
Design for Environment (DfE) is a product development approach that encompasses environmentalmanagement principles covering the entire product cycle and can be a tool to reduce the environmental impact and minimize the resources used in the making of a product. Faced with the pressure of society and governments on organizations to develop products and services that reduce environmental impacts, the dissemination of studies on the adoption of DfE practices can contribute to the lifecycle management of the product. Electronic products are characterized by quick popularization, quick obsolescence, and trend for tech aficionados. However, the fast replacement of these products, as well as their disposal, can lead to serious environmental problems due to the long term required for components decomposition. The problem is exacerbated by the lack of appropriate disposal sites for many obsolete products. In this way, DfE can reduce the environmental impacts of electronic products throughout its development cycle. In this context, this article aims to identify DfE practices theoretically and analyze the adoption of these practices in the electronic sector. A systematic review of the DfE literature thus allowed to identify several practices that were categorized in the product development cycle. Subsequently, a case study was conducted in an electronics company, with the purpose of empirically observing the adoption of DfE practices. The theoretical research and the empirical study allowed to observe the practices adopted and the context of the application of DfE in the product development cycle. The customer has a strong influence on product functionality, which affects some decisions by the electronics industry, especially in the usage phase of the product.